Formation of Abstract Principles of Morality - Kapačiauskienė, Danutė (Problemos, 1974)
The paper analyses the formation process of bourgeois moral principles (the principles of humanism) as one of formation of theoretical, abstract, and pure moral ideas. In the epoch of feudalism due to poverty of the commodity relation system the ideological process was not of purely theoretical nature, free of concrete social content. Moral principles did not constitute then a separate relatively independent domain of ideology. Generally, social values were characteristically syncretic. The development of capitalism and its system of social relations engenders the formation of principles of abstract humanism called upon to defend the interests of the bourgeoisie. The abstract character of ideology is overcome by the principles of socialist morality for they acquire the concrete content and express the definite programme of social reconstruction.